Effects of Slag Applications and Salinity Stress on Greenhouse Durum Wheat (Triticum durum Desf.) Plants - Errouh, Farid; Aouabe, Abdelhamid; Sadouki, Ayoub; Chagiri, Hassan; Khalisse, Hicham; Oudra, Brahim; Rodriguez, Julio Cesar; Er-Raki, Salah; Meddich, Abdelilah (European Scientific Journal, ESJ, 2023)
The search for sustainable practices to increase productivity is a fundamental need in current agriculture. Steel slag has been studied for its potential use in agriculture. These substances present a great ability of agricultural applications since they are rich in nutrients. The effect of steel slag-based fertilizer was investigated on greenhouse durum wheat cultivar under salt-stress conditions. Two doses of slag: 10 g slag/ kg soil (D1) and 20 g slag/ kg soil (D2) were evaluated under no salt-stress (0 mM NaCl) and salt-stress conditions (100 mM NaCl) for salinity stress mitigation. Morpho-physiological and biochemical parameters of wheat were measured and compared to the different treatments. Exposure of wheat to salinity decreased its biomass, stomatal conductance, efficiency of photosystem II, and protein content, but it increased total soluble sugars, hydrogen peroxide (H2O2), and malondialdehyde (MDA) contents. Amended plants with 10 g slag/ kg soil (D1) led to a significant improvement in biomass with an increase of shoot and root dry weights (133% and 400% respectively), stomatal conductance (22 %), soluble sugars (14 %), and protein content (158%) under saline conditions compared to the control treatment with 0 g slag/ kg soil (C), thus indicating a positive influence on durum wheat plants. Soil enrichment with 20 g slag/kg soil (D2) decreased plant growth parameters and presented the highest levels of H2O2 and MDA contents compared to the control and treatment (D1) after three months of cultivation under salt stress. This study supports the hypothesis of the application of slag at lower dose, which improves productivity of durum wheat and mitigate salinity stress.